A Study on graph with Desmos through Ict in diploma in elementary education of tamil Nadu state board - Charles Paul, P.; Thulasi, G. (International Journal of Engineering and Technology, 2017)
This paper aims at bringing out the skill based learning outcomes in teaching learning process specific to psychomotor domain throughÂ Â ICTâ€™sÂ Â based on New Educational Technology 2013. The present study intends to apply the DesmosÂ Â software to teach the Linear Graph chapter in Diploma in Elementary Education (D.El.ED) of Second year in Tamil Nadu State. It explains the teaching strategies, i.e. visualization of graphical structure with the above module. Desmos gives hands-on experience to understand the mathematical, Graphical concepts. It also aims for an extended study on Algebra, Statistics and Geometry in the second year source book prescribed for the (D.El.ED) Course of Tamil Nadu State Board.